Performance Analysis of Handover Initiation Parameters in Long Term Evaluation – Advanced (LTE-A) Network - Yusof, Azita Laily; Zainali, Muhammad Aiman; Yaacob, Nor Suzila (International Journal of Integrated Engineering, 2022)
In mobile network, mobility management plays an important role in order to support seamless handover in Long Term Evolution - Advanced (LTE-A) network. It is predicted that in the near future there will be an increase demand of voice and data traffic. Currently, LTE-A network purely depends on the hard handover that may cause disconnection to occur if the handover is not fast enough. When handover executes, it may experience failure because of the early handover, the late handover or handover to wrong cell. Thus, the cases of packet loss or communication interruption problems will occur. In this research, handover initiation parameters in LTE-A network is investigated. Firstly, a formulation of analytical framework has been developed to analyze the handover performance. Then, mathematical equations have been derived from the developed framework by incorporating the value of user’s speed and handover signaling delay parameters. Under this framework, the probabilities of handover failure were analyzed in order to observe the handover performance when the speed of user is increased. The numerical results show that if fixed value of Reference Signal Receive Power (RSRPth) is used, the number of handover failures increased as the speed increased. It also shows that it is essential to predict the handover signalling delay in advance to reduce the handover failure rate in LTE- A network.